2018
DOI: 10.1002/tox.22551
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide, an oral antihelmintic drug, exhibits antimetastatic activity in hepatocellular carcinoma cells through downregulating twist‐mediated CD10 expression

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies in the world, especially, in eastern Asia, and its prognosis is poor once metastasis occurs. Niclosamide, a US Food and Drug Administration-approved antihelmintic drug, was shown to inhibit the growth of various cancers including HCC, but the effect of niclosamide on cell motility and the underlying mechanism have not yet been completely defined. The present study demonstrated that niclosamide, at 0-40 nM, concentration-dependently inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Firstly, we found that niclosamide significantly reduced proliferation of GBM TSs in a dose dependent manner. Chien et al ( 2018 ) reported that niclosamide inhibited invasiveness but could not alter cell viability in hepatocellular carcinoma. However, several studies have revealed that niclosamide inhibits the proliferation of cancer cells in colon (Sack et al 2011 ), breast (Londono-Joshi et al 2014 ), prostate (Lu et al 2011 ), and lung cancers (Stewart et al 2016 ), as well as GBM (Wieland et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we found that niclosamide significantly reduced proliferation of GBM TSs in a dose dependent manner. Chien et al ( 2018 ) reported that niclosamide inhibited invasiveness but could not alter cell viability in hepatocellular carcinoma. However, several studies have revealed that niclosamide inhibits the proliferation of cancer cells in colon (Sack et al 2011 ), breast (Londono-Joshi et al 2014 ), prostate (Lu et al 2011 ), and lung cancers (Stewart et al 2016 ), as well as GBM (Wieland et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…354 An increasing number of studies have shown niclosamide has an anti-metastasis effect in oral squamous cell carcinoma, hepatocellular carcinoma, melanoma, and human thyroid cancer. [355][356][357][358] A Phase II clinical trial of niclosamide, in which the drug was applied to patients with colorectal cancer metastases, has been conducted to assess the drug safety and efficacy (NCT02519582). Clinical trials have also been conducted for the treatment of prostate cancer (NCT02532114) (NCT03123978).…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Several studies have reported that the MAPK signaling is known to regulate MMP‐9 expression and play a vital role in HCC metastasis 45–47 . Western blot revealed that kaempferol (0, 25, 50, 75, and 100 μM) had no obvious influence on the expressions of p‐p‐38, total p‐38, p‐ERK1/2, total ERK1/2, p‐JNK1/2 and total JNK1/2 in Huh‐7 and SK‐Hep‐1 cells (Figure 6A and B).…”
Section: Resultsmentioning
confidence: 94%